Total phenolic, total flavonoid content and antioxidant efficacy of leaves of eupatorium adenophorum - Y.C. TRIPATHI,; NIDHI SAINI, (International Journal of Pharma and Bio Sciences, 2019)
The study was aimed to evaluate the total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity of different extracts of Eupatorium adenophorum leaves to find out the most advantageous solvent for extraction of antioxidants. The percentage yield of petroleum ether, chloroform, ethyl acetate, acetone, methanol and hydro-methanol (Aq. methanol) extracts ranged from 8.67±1.23 to 17.43 ± 1.55 (dw). The solvent, hydro-methanol (Methanol: Water-9:1) yielded the highest amount of extract followed by methanol. Phytochemical screening indicated the presence of various group of phytochemicals in different extracts. Methanol extract recorded the maximum number of chemical constituents. Based on phytochemical screening, chloroform, ethyl acetate, acetone, methanol and hydro-methanol extracts were evaluated for TPC, TFC and antioxidant activity. Among the extracts studied, the TPC and TFC were found in the range of 30.71±0.16 − 68.51±0.58 mg GAE/g and 18.93±1.76 − 32.25±1.15 mgQE/g respectively. Both TPC and TFC were at the highest in hydro-methanol extract followed by methanol extract. All extract exhibited varying degree of DPPH radical scavenging activity and reducing potency in a dose dependent fashion. The hydro-methanol extract displayed the highest radical scavenging activity and reducing power. Both radical scavenging activity and reducing power followed the order of hydro-methanol Ëƒ methanol Ëƒ acetone Ëƒ ethyl acetate Ëƒ chloroform. The antioxidant property of E. adenophorum leaves extracts as determined in the present study might be useful for the development of newer and more potent antioxidants.